1987
DOI: 10.1111/j.1744-313x.1987.tb00360.x
|View full text |Cite
|
Sign up to set email alerts
|

Hla Expression on Human Germinal Cells

Abstract: SUMMARY Ejaculated human seminal plasma cells obtained from 46 healthy men and 48 infertile patients were tested for expression of HLA class I and II antigens by complement‐mediated cytotoxicity, cell‐binding radioimmunoassay (CB‐RIA), and an ELISA involving monoclonal antibodies (mAbs). In a group of healthy men tested for HLA expression on human spermatozoa, 4 of 46 were positive for class I and II HLA antigens. However, the results were negative in a second examination of the same donors, possibly on accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…Transcription of HLA-F was only visible after prolonged exposure of the autoradiograms and at least 100-fold less than in KR cells and human PBL (data not shown). The antisense oligonucleotide probe o-LG2-C1 [16] specific for the HLA-E locus hybridized with the two HLA-E transcripts of 1800 and 2700 nucleotides in size. A strong hybridization signal was visible in the mRNA from PBL (L2,L3) and from the human B-LCL, KR (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcription of HLA-F was only visible after prolonged exposure of the autoradiograms and at least 100-fold less than in KR cells and human PBL (data not shown). The antisense oligonucleotide probe o-LG2-C1 [16] specific for the HLA-E locus hybridized with the two HLA-E transcripts of 1800 and 2700 nucleotides in size. A strong hybridization signal was visible in the mRNA from PBL (L2,L3) and from the human B-LCL, KR (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In these early reports alloantisera (of doubtful specificity) were used; however, a more complex situation arose in reports where monoclonal antibodies were employed. Relatively recent data mostly negated the presence of human MHC class I molecules on the surface of testicular germ cells [13-151. However, these studies indicated the possibility of HLA [I 164301 ~~ induction in gametogenic cells from patients with azoospermia, possibly due to factors activating the immune response such as viruses or cytokines [16]. Since evidence has been provided that sperm precursor cells generated during normal spermatogenesis do not seem to express surface HLA molecules, the presence of these antigens on finally differentiated spermatozoa became even more doubtful [17,181.…”
Section: Introductionmentioning
confidence: 98%
“…This could explain the finding of some authors that MHC antigens on sperm of mice and humans seem to be haploid expressed (Fellous & Dausset, 1970;Halim & Festenstein, 1975;Arnaiz-Villena & Festenstein, 1976;Halim et al, 1982). On the other hand, however, several groups could not find any MHC antigens on human sperm (Haas & Nahhas, 1986;Kuhlman et al, 1986), and others found MHC antigens on human sperm of only few individuals of a sample (Kurpisz et al, 1987), or found only some HLA-A and -B antigens but not others (RodrIguezCórdoba & Arnaiz-Villena, 1985). A possible explanation for these controversial findings could be that haploid expression of MHC on sperm is conditiondependent, e.g.…”
Section: Introductionmentioning
confidence: 94%
“…The expression of class I HLA molecules by human spermatozoa is controversial ( Kurpisz, 1987; Kurpisz & Fernandez, 1992; Fiszer & Kurpisz, 1998; Hutter & Dohr, 1998). In the last two decades, the presence of these molecules on spermatozoa has been reported in a large number of papers using cytotoxicity tests ( Rodriguez‐Cordoba & Arnaiz‐Villena, 1985; Kurpisz et al ., 1987 ), fluorescent‐labelling techniques ( Bishara et al ., 1987 ), enzyme‐linked immunosorbent assay (ELISA) ( Bishara et al ., 1987 ; Kurpisz et al ., 1987 ), or cellular binding radioimmunoassay (CB‐RIA) ( Kurpisz et al ., 1987 ). An equal number of papers have reported spermatozoa to be negative for class I HLA using fluorescent‐labelling techniques ( Haas & Nahhas, 1986; Kuhlmann et al ., 1986 ; Jassim et al ., 1989 ; Schaller et al ., 1993 ), ELISA ( Schaller et al ., 1993 ) and CB‐RIA ( Anderson et al ., 1982 ; Kowalik et al ., 1989 ; Ohashi et al ., 1990 ).…”
Section: Introductionmentioning
confidence: 99%